A mesh free method using rectangular pre-solved domains using Kronecker products. Issue 1 (2nd January 2017) - Shojaei, I.; Rahami, H.; Kaveh, A.
ABSTRACT: In this paper, a mesh free algorithm using large pre-solved domain is developed. Using the largest rectangle inside an arbitrary domain, a pre-solved rectangular domain is established using Kronecker product and graph theory rules. This pre-solved domain is efficiently inserted into the mesh free formulation of partial differential equations (PDEs) and engineering problems to reduce the computational complexity and execution time of the solution. The general solution of the pre-solved rectangular domain is formulated for second-order shape functions. The efficiency of the present algorithm depends on the relative size of the large rectangular domain and the main domain; however, the method remains as efficient as a standard method for even small relative sizes. For adaptive procedures with nonuniform density of distributed points in the domain, smaller (e.g. sub-maximal) rectangular domain can be used. The application of the method is demonstrated using some examples.